The forecast of development of the liquid fuels - Biernat, Krzysztof (Studia Ecologiae et Bioethicae, 2005)
The article includes analysis o f basic terms an d definitions an d following issues: the directions of modification and development of the drive in the wheel vehicles, the forecast of development of standard fuels for internal combustion engines, the improvement of demands towards oils and fuel liquids, prospective fuel substances and non-standard fuels.